lkpd pjbl-socioscientifik issue EFEKTIVITAS LKPD BERBASIS PJBL-SOCIOSCIENTIFIK ISSUES MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN TERHADAP KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK SMA/MA: artikel ini menjelaskan tentang efektivitas lkpd pjbl-socioscientifik issues materi perubahan dan pelestarian lingkungan terhadap kemampuan berpikir kreatif peserta didik kelas X fase E - Messy Naitul; Arsih, Fitri (Al-Alam: Islamic Science Education Journal, 2025)
The 4D development methodology, which consists of the stages of define, design, develop, and disseminate, can be used to create LKPD based on PjBL-Socioscientific Issues with the topic of environmental change and conservation. The research carried out by Rahmawati has produced LKPD to the development stage, so further research is needed for the disseminate stage, one of which is through effectiveness testing. Quasy experiment is the method used in this study, with a pretest-postest control group as the design. The population taken in this study is all phase E students at SMAN 12 Padang. The samples were randomly selected, with class E5 being the experimental group while E2 being the control group. The data collected were in the form of test results of students' creative thinking skills, which were measured using a description test instrument that had been tested for validity and reliability. The Mann Whitney U Test and the N-gain Test were used as data analysis in this study. The results showed that the average creative thinking ability of students in the experimental class was significantly higher than that of the control class. The hypothesis test with the Mann Whitney U test yielded a significance value of 0.000. The results of the N-gain test in the experimental class were 55% in the medium category, while in the control class was 37% in the medium category. Thus, it can be concluded that the PJBL-Socioscientific Issues Based LKPD on environmental change and conservation materials improves the results of the creative thinking skills of phase E students of SMAN 12 Padang